MENGOPTIMALKAN PEMBELAJARAN: LITERATURE REVIEW PERMAINAN TRADISIONAL BERBASIS ETNOPEDAGOGIK DALAM PEMBELAJARAN SAINS DAN SOSIAL DI SEKOLAH DASAR - Rizal Taufik; Meirin Dwiningtyas Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Every region in Indonesia has a variety of traditional games that have become an integral part of daily life and local cultural heritage. Besides serving as a means of entertainment, traditional games also have significant potential as learning media, particularly in developing science and social competencies at the elementary school level. This research uses a qualitative approach with a literature study method, a method that allows researchers to gain an in-depth understanding of a phenomenon through the analysis of relevant documents, texts, and literature sources. The results show that integrating traditional games into science and social learning can address various learning challenges. The inclusion of these games not only provides a fun learning experience and increases student motivation, but also supports the development of social skills, physical abilities, and the internalization of cultural values. Furthermore, traditional games play a role in shaping students' character through training in cooperation, discipline, and ethics, thus becoming a holistic and effective learning tool in elementary schools.